What Works? A Meta Analysis of Recent Active Labor Market Program Evaluations - David Card; Jochen Kluve; Andrea Weber (Institute for the Study of Labor (IZA), 2015)
We present a meta-analysis of impact estimates from over 200 recent econometric evaluations of active labor market programs from around the world. We classify estimates by program type and participant group, and distinguish between three different post-program time horizons. Using meta-analytic models for the effect size of a given estimate (for studies that model the probability of employment) and for the sign and significance of the estimate (for all the studies in our sample) we conclude that: (1) average impacts are close to zero in the short run, but become more positive 2-3 years after completion of the program; (2) the time profile of impacts varies by type of program, with larger gains for programs that emphasize human capital accumulation; (3) there is systematic heterogeneity across participant groups, with larger impacts for females and participants who enter from long term unemployment; (4) active labor market programs are more likely to show positive impacts in a recession.
Keywords: J00; J68; 330; active labor market policy; program evaluation; meta-analysis